The Role of School Libraries in Improving Information Literacy in Children: A Systematic Literature Review - Firmansyah, Ali; Alaauddin, Akmal Insan (Universitas Negeri Padang, 2024)
Libraries are considered important to be able to manage, organize, store and collect collections of library materials systematically which are used as a source of information by users. The school library is a place of information especially for students, teachers and other school members. Through information literacy students will be able to learn independently, because it involves recognising when information is needed and being able to efficiently search, accurately evaluate, effectively use, and clearly communicate. The research method used was systematic literature review (SLR) and researchers conducted a literature search using the Publish or Perish (PoP) application using the Google Scholar database by reviewing with a search strategy using the keywords